Respuesta :

Answer:

-2

Step-by-step explanation:

5-(1-5÷(-5)(5+1))

Work the parentheses from the inside out

5-(1-5÷(-5)*6)

Them the Work inside the last parentheses and multiply and divide from left to right

5-(1-5÷(-5)*6)

5 divided by -5 = -1

5-(1-(-1))*6)

-1 * 6 = -6

5-(1- -6)

Then subtract

1 - -6 = 1+6 = 7

5 - (7)

Subtract

-2

Answer:

[tex]\Huge \boxed{-2}[/tex]

Step-by-step explanation:

[tex]\displaystyle 5-(1-\frac{5}{-5} (5+1) )[/tex]

Solving for brackets.

[tex]\displaystyle 5-(1- (-1)(6))[/tex]

[tex]\displaystyle 5-(1+6)[/tex]

[tex]5-7[/tex]

Subtracting both numbers.

[tex]=-2[/tex]